In-core thermal and fast neutron measurements with 4H-SiC P+N junction diodes in the JSI TRIGA Mark II research reactor - Valero Valentin; Ottaviani Laurent; Lyoussi Abdallah; Destouches Christophe; Radulović Vladimir; Snoj Luka; Volte Adrien; Carette Michel; Reynard-Carette Christelle (EPJ Nuclear Sciences & Technologies)
Accurate online in-core parameter measurements, such as neutron and photon fluxes and nuclear heating rates, are essential for fusion and fission applications. Wide bandgap semiconductors, particularly Silicon Carbide (SiC), have demonstrated strong potential for radiation detection over six decades. Despite this, challenges persist in optimizing detector performance under extreme in-core conditions. Our study focuses on 4H-SiC-based detectors, developed within a joint laboratory between Aix-Marseille University and the CEA, aiming to address these challenges and provide high-precision measurements for advanced nuclear facilities. Following previous measurements in ZPRs and with D-T neutron generators, this paper focuses on in-core experimental results obtained with such detectors in the Triangular Irradiation Channel (TIC) of the TRIGA Mark II-type research reactor at the Jožef Stefan Institute (JSI) in Slovenia. These in-core measurements were done by using two types of diodes. One with a Neutron Converter Layer (NCL) of Boron-10 for thermal neutron detection, and the other one without NCL in order to discriminate thermal and fast neutrons by studying 10B reaction versus scattering. Thanks to various Pulse Shape Analyses (PSA) and count rate studies the influence of bias voltage, NCL and neutron fluence on the detector performances were determined. The highest neutron flux and fluence for these detectors were reached: 1.2 × 1013 cm−2·s−1 and 1.2 × 1017 cm−2, respectively.